Pengaruh Substitusi Tepung Sukun pada Pembuatan Nugget Ayam Kampung terhadap Kualitas Kimia dan Organoleptik: The effect of Breadfruit Flour Substitution in the Making Native Chicken Nuggets on Chemical Quality and Organoleptic - Wilda Sete; Geertruida M Sipahelut; Yakob R Noach; Tri Rizkie Zainal (Universitas Nusa Cendana, 2023)
This study aims to determine the effect of substitution of wheat flour with breadfruit flour in native chicken nuggets. The method used was an experimental method with a Completely Randomized Design (CRD) consisting of 4 treatments 4 replications P0 = 0%, P1=10%, P2=15, P3=20%. The observed variables were protein, fat, crude fiber content, yield, organoleptic quality and level of preference. Data were analyzed using ANOVA then continued with Duncan's test to determine differences between treatments and nonparametric test using Kruskal-Wallis followed by Mann Whitney. The results showed that breadfruit flour substitution had a significant effect (P<0.05) on protein, fat, yield, while it had a significant effect (P<0.01) on fiber content, color, aroma, taste, texture and preference level. The best breadfruit flour substitution was 20% (P3) with a protein content percentage of 20.30%, fat content of 7.86%, protein content fiber by 1.09%. While the organoleptic value of color and texture, the level of preference for village chicken nuggets with the addition of breadfruit flour was the best in treatment P1 (10%). The addition of breadfruit flour on native chicken nuggets until level 20% can increase protein content, fat content, fiber content. The addition of 10% breadfruit flour was the best for organoleptic tests and level of liking. Free range chicken nuggets whit 10%, 15%, 20% breadfruit flour substitution produce protein content and fat content that meet the content set by SNI. Penelitian inibertujuan untuk mengetahui pengaruh substitusi tepung terigu dengan tepung sukun pada nugget ayam kampung. Metode yang digunakan adalah metode percobaan dengan Rancangan Acak Lengkap (RAL) terdiri dari 4 perlakuan 4 ulangan. Perlakuan P0 = 0% P1 = 10%, P2= 15%, P3= 20%. Variabel yang diamati meliputi protein, lemak, kadar serat, rendemen, mutu organoleptik dan tingkat kesukaan. Data dianalisis menggunakan ANOVA kemudian dilanjutkan dengan uji Duncan untuk mengetahui perbedaan antar perlakuan dan uji nonparametik menggunakan Kruskal-Wallis dilanjutkan dengan Mann Whitney. Hasil penelitianmenunjukkan bahwa substitusi tepung sukun berpengaruh nyata (P<0,05) terhadap protein, lemak, rendemen sedangkan sangat berpengaruh nyata (P<0,01) terhadap kadar serat, warna, aroma, rasa, tekstur dan tingkat kesukaan. Substitusi tepung sukun terbaik sebanyak 20% (P3) dengan persentasi kandungan protein 20,30%, kandungan lemak 7,86%, kadar serat 1,09%. Sedangkan nilai organoleptik warna dan tekstur, tingkat kesukaan nugget ayam kampung dengan penambahan tepung sukun terbaik pada perlakuan P1 (10%). Penambahan tepung sukun pada nugget ayam kampung sampai level 20% meningkatkan kandungan protein, kandungan lemak, kadar serat. Penambahan tepung sukun sebanyak 10% terbaik untuk uji organoleptik dan tingkat kesukaan. Nugget ayam kampung dengan substitusi tepung sukun 10%, 15%, 20% menghasilkan kandungan protein, kandungan lemak yang telah memenuhi kandungan yang di tetapkan SNI.